The Sex Features of Patients With Solid Pseudopapillary Neoplasms of the Pancreas: A Retrospective Study - Wei, Guangmin; Luo, Qiong; Fang, Jiankai; Li, Xiaolou; Shi, Yanhong; Li, Yuqiong; Sun, Liqi (Frontiers in Oncology, 2022)
Background: Solid pseudopapillary neoplasms （SPNs）of the pancreas in male patients are more frequently reported. The aim of the study was to evaluate the sex features of SPN and the risk factors that predict tumor recurrence. Methods: From 2013 to 2019, patients who were pathologically confirmed to have SPNs were retrospectively reviewed. The baseline study parameters were compared between males and females. A logistic regression model was established to identify the independent risk factors for tumor recurrence. Results: In total, 221 patients were included in this study. Of them, 53 patients (24.0%) were males. Male patients were older than female patients (39.1 vs 31.6 years, P=0.001), and the tumor size in male patients was smaller than that in female patients (39.65vs 50.38mm, P=0.038). The preoperative imaging diagnostic accuracy was significantly higher in females than in males (70.5% vs 54%, P=0.02). SPNs in male patients tended to be misdiagnosed with other malignant tumors (37.7% vs 10.7%, P<0.0001), with a more solid component observed in images (66.8% vs 24.7%, P<0.0001). For immunohistochemical staining, the expression of beta catenin was significantly lower in male patients (P=0.002), and the expression of vimentin was the opposite (P=0.01). The overall survival rate and disease-free survival were not different. Based on multivariate analysis, older age [hazard ratio (HR)= 1.094, 95% confidence interval (CI): 1.005-1.190] and KI 67 index grade III (HR=12.029, 95% CI: 2.399-60.311) were independent risk factors for tumor recurrence. Conclusion: The clinical and imaging features of SPN in males were not in full accord with those in females; however, the differences did not influence prognosis.